2017
DOI: 10.3390/polym9030084
|View full text |Cite
|
Sign up to set email alerts
|

Superiorly Plasticized PVC/PBSA Blends through Crotonic and Acrylic Acid Functionalization of PVC

Abstract: Superior plasticization efficiency was achieved by a grafting from functionalization of the PVC backbone. This was deduced to a synergistic effect of internal plasticization and improved intermolecular interactions between PVC and an oligomeric poly(butylene succinate-co-adipate) (PBSA) plasticizer. A mild grafting process for functionalization of the PVC chain by crotonic acid (CA) or acrylic acid (AA) was used. The formation of PVC-g-CA and PVC-g-AA was confirmed by FTIR and 1 H NMR. Grafting with the seemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…PVC modication through the graing of acrylic acid represents an efficient route for materials properties enhancement, especially when considering membrane technologies or biomedical applications. [33][34][35][36][37] PVC -acrylic acid graing can be achieved by different routes such as plasma or electron beam facilitated graing of poly(acrylic acid), 14,27,33,35,38 photoinduced radical polymerization, 39 use of chemically induced physisorbed radical species, 36,40 in situ chlorinating gra copolymerization 41 and controlled polymerization reactions. However, in the case of controlled polymerization techniques for the fabrication of polyacrylic acid gras, the carboxyl functionality is usually obtained using a post-polymerization hydrolysis stage.…”
Section: Introductionmentioning
confidence: 99%
“…PVC modication through the graing of acrylic acid represents an efficient route for materials properties enhancement, especially when considering membrane technologies or biomedical applications. [33][34][35][36][37] PVC -acrylic acid graing can be achieved by different routes such as plasma or electron beam facilitated graing of poly(acrylic acid), 14,27,33,35,38 photoinduced radical polymerization, 39 use of chemically induced physisorbed radical species, 36,40 in situ chlorinating gra copolymerization 41 and controlled polymerization reactions. However, in the case of controlled polymerization techniques for the fabrication of polyacrylic acid gras, the carboxyl functionality is usually obtained using a post-polymerization hydrolysis stage.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(vinyl chloride) (PVC) is a kind of thermoplastic polymer manufactured by the polymerization of vinyl chloride monomer. It has extensive applications in the living and industrial fields because of its advantages for mature production technology, easy to process molding, corrosion resistance, abrasion resistance, flame retardant properties, and good electrical insulating performance [1,2,3]. However, the HCl can be easily removed from the structure of PVC, because the molecule contains allylic and tertiary chlorine atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(vinyl chloride) (PVC) is one of the five general plastics, and has been widely used in infrastructure construction and home supplies because of its excellent low cost, high strength, corrosion resistance, and self-extinguishing capability, etc. [1]. In applications, its poor thermal stability is the biggest weakness of PVC.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we synthesized a series of polyol-based metal alkoxides as PVC thermal stabilizers, and showed that they were efficient in inhibiting the degradation of PVC [24,25]. There is still a challenge for these polyol-based metal alkoxides to be used as PVC thermal stabilizers, because their melting point (about 220 °C) [1,2] is significantly higher than the processing temperature of PVC, affecting their consistency with PVC [26]. In order to reduce the melting point of polyol-based metal alkoxides, Shentu et al employed mannitol with a low melting point of 166 °C to synthesize mannitol-zinc metal alkoxides, which was then used to improve PVC thermal stability [2].…”
Section: Introductionmentioning
confidence: 99%